Magnusiomyces doitungensis sp. nov., a novel arthroconidial yeast isolated from rotten wood in Northern Thailand - Linn, Maung M.; Bhunjun, Chitrabhanu S.; Khunnamwong, Pannida; Boekhout, Teun; Hyde, Kevin D. (Phytotaxa, 2026)
A biodiversity and taxonomic study of yeast isolates collected from rotten wood in Northern Thailand, revealed the presence of a novel yeast species. Morphology, phylogeny, and physiological and biochemical characteristics revealed it as a novel species of Magnusiomyces. According to maximum likelihood and Bayesian inference analyses of the combined dataset of internal transcribed spacer (ITS) and the D1/D2 domains of the large subunit (LSU) regions, our isolate formed an independent clade within Magnusiomyces. Biochemical and physiological characteristics confirmed that there are some carbon and nitrogen assimilation differences compared to the closely related species M. fungicola, M. gigas, M. japonicus, M. suaveolens, M. magnusii, M. tetrasperma, and M. pitmudophilus. Therefore, by using a polyphasic approach, incorporating morphology, phylogeny, physiology, and biochemical analysis, we recognize Magnusiomyces doitungensis as a new species.